Dental Stem Cells SV40, a new cell line developed in vitro from human stem cells of the apical papilla. (12th January 2023) - Sanz‐Serrano, Diana; Sánchez‐de‐Diego, Cristina; Mercade, Montse; Ventura, Francesc
Abstract: Aim: To establish and fully characterize a new cell line from human stem cells of the apical papilla (SCAPs) through immortalization with an SV40 large T antigen. Methodology: Human SCAPs were isolated and transfected with an SV40 large T antigen and treated with puromycin to select the infected population. Expression of human mesenchymal surface markers CD73, CD90 and CD105 was assessed in the new cell line named Dental Stem Cells SV40 (DSCS) by flow cytometry at early and late passages. Cell contact inhibition and proliferation were also analysed. To evaluate trilineage differentiation, quantitative polymerase chain reaction and histological staining were performed. Results: DSCS cell flow cytometry confirmed the expression of mesenchymal surface markers even in late passages [100% positive for CD73 and CD90 and 98.9% for CD105 at passage (P) 25]. Fewer than 0.5% were positive for haematopoietic cell markers (CD45 and CD34). DSCS cells also showed increased proliferation when compared to the primary culture after 48 h, with a doubling time of 23.46 h for DSCS cells and 40.31 h for SCAPs, and retained the capacity to grow for >45 passages (150 population doubling) and their spindle‐shaped morphology. Trilineage differentiation potential was confirmed through histochemical staining and gene expression of the chondrogenic markers SOX9 and COL2A1, adipogenic markers CEBPA and LPL, and osteogenic markers COL1A1 and ALPL . Conclusions: The new cell line derived from human SCAPs has multipotency, retains its morphology and expression of mesenchymal surface markers and shows higher proliferative capacity even at late passages (P45). DSCS cells can be used for in vitro study of root development and to achieve a better understanding of the regenerative mechanisms.